Impact of a Tertiary Eligibility Threshold on Tertiary Education and Earnings: A Discontinuity Approach - Martin Nordin; Gawain Heckley; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2017)
This study evaluates the impact of achieving tertiary eligibility in upper-secondary education on tertiary education and earnings in Sweden. Using a regression discontinuity design, we estimate the impact of tertiary eligibility and show that it has a substantial impact on the probability of enrolling in tertiary education. For students who achieve tertiary eligibility, the probability of enrolling in tertiary education increases by around 15 and 7 percentage points for an academic and vocational track, respectively. This implies (before age 30) around 8 percent higher earnings (at the intensive margin) for men on an academic track, while for women on an academic track it increases the probability of having positive incomes (the extensive margin) by around 3 percent. Thus, we conclude that (academic) students at the margin of eligibility for enrolling in tertiary education receive a substantial tertiary education payoff.
Keywords: I21; I26; I28; 330; Tertiary education; upper-secondary education; earnings; eligibility; regression discontinuity design